Radiographic fibrosis score predicts survival in systemic sclerosis‐associated interstitial lung disease. Issue 4 (19th September 2017) - Takei, Reoto; Arita, Machiko; Kumagai, Shogo; Ito, Yuhei; Tokioka, Fumiaki; Koyama, Takashi; Saito, Rintaro; Nishimura, Keisuke; Tokumasu, Hironobu; Ishida, Tadashi
ABSTRACT: Background and objective: Interstitial lung disease (ILD) is a common pulmonary manifestation of systemic sclerosis (SSc). It is unknown whether radiographic fibrosis score predicts mortality in SSc‐associated ILD (SSc‐ILD). We retrospectively analysed patients with SSc‐ILD to evaluate whether radiographic fibrosis score was a useful predictor of mortality. Methods: We identified SSc‐ILD patients evaluated at Kurashiki Central Hospital (Japan) from 2006 to 2016, and radiographic fibrosis scores based on the extent of reticulation and honeycombing on high‐resolution computed tomography (HRCT) scanning were calculated by manually tracing around each fibrotic area. Independent predictors of overall survival were determined using the Cox proportional hazards model. Results: The study included 48 patients, of whom 19 had usual interstitial pneumonia on HRCT. The median follow‐up period was 56.6 months, and over the follow‐up period 15 patients died. The 5‐year survival was 72.4%. In the multivariate analysis, radiographic fibrosis score, age, being male and forced vital capacity were independently associated with an increased risk of death, while HRCT pattern was not. Conclusion: A high radiographic fibrosis score was a poor prognostic factor in SSc‐ILD. More widespread fibrosis was associated with an increased risk of death, independent of HRCT pattern. Abstract : It is unknown whether radiographic fibrosis score predicts mortality in systemic sclerosis‐associated interstitial lung disease. This study shows that a high radiographic fibrosis score was a poor prognostic factor. More widespread fibrosis was associated with an increased risk of death, independent of high‐resolution computed tomography pattern.